Targeting the PI3K/Akt/mTOR Pathway in Hepatocellular Carcinoma - Eun Jin Sun; Miriam Wankell; Pranavan Palamuthusingam; Craig McFarlane; Lionel Hebbard (Biomedicines, 2021)
Despite advances in the treatment of cancers through surgical procedures and new pharmaceuticals, the treatment of hepatocellular carcinoma (HCC) remains challenging as reflected by low survival rates. The PI3K/Akt/mTOR pathway is an important signaling mechanism that regulates the cell cycle, proliferation, apoptosis, and metabolism. Importantly, deregulation of the PI3K/Akt/mTOR pathway leading to activation is common in HCC and is hence the subject of intense investigation and the focus of current therapeutics. In this review article, we consider the role of this pathway in the pathogenesis of HCC, focusing on its downstream effectors such as glycogen synthase kinase-3 (GSK-3), cAMP-response element-binding protein (CREB), forkhead box O protein (FOXO), murine double minute 2 (MDM2), p53, and nuclear factor-κB (NF-κB), and the cellular processes of lipogenesis and autophagy. In addition, we provide an update on the current ongoing clinical development of agents targeting this pathway for HCC treatments.